The Drive Behind Dough: Women’s Motivational Structures and Social Transformation through Traditional Pastry Enterprises in Rural Aceh - Dearahim, Dewingga; Zulkarnain, Zulkarnain; Zulkarnaini, Zulkarnaini; Yunus, Wan Muhammad; Juliansyah, Rollis (Universitas Pattimura, 2025)
This study aims to identify and describe the motivation levels of women engaged in traditional cake businesses in Gampong Langung, Meureubo Subdistrict, West Aceh Regency, and to reveal the dominant needs driving their entrepreneurial activities. The research is grounded in the critical role of home-based traditional cake enterprises as a source of supplementary income, contributing to family welfare and women’s social transformation in rural settings. A quantitative descriptive approach was employed, using a Likert-scale questionnaire (1–5) with 15 items representing Maslow’s five hierarchical needs: physiological, safety, social, esteem, and self-actualization. Findings show that 40% of respondents have high motivation, 40% moderate, and 20% low. Physiological and safety needs recorded the highest scores, while self-actualization scored the lowest. Most entrepreneurs are driven by economic necessity and family stability, with self-fulfillment motivations still emerging. Highly motivated individuals tend to have family support, income growth, and long-term business orientation, while those with low motivation face barriers that hinder entrepreneurship. This study’s novelty lies in mapping the motivational structure of rural women entrepreneurs in Aceh and reinforcing Maslow’s theory in the context of community-based economic empowerment. It recommends need-based strategies to enhance motivation, promote sustainable growth, and support women’s social transformation and rural economic independence.